Transformation induced plasticity (TRIP) due to precipitation during continuous tempering of quenched and tempered steels - Niki Nouri; Elena Hillenmeyer; Thanusan Thavarajan; Stefan Dietrich; Volker Schulze (Journal of Materials Research and Technology)
Heat treatment is an essential step in achieving the desired characteristics in steels. Quenched and tempered (Q&T) steels are often tempered to adjust the strength-ductility ratio by taking advantage of the precipitation of carbides. In practice, many parts already contain residual stresses, for example due to the temperature gradients during surface hardening, and therefore tempering takes place under the influence of these stresses. The occurring transformation induced plasticity (TRIP) means significant plastic deformation during a phase transformation under a stress below the material’s yield strength. In this work, tempering TRIP of three different Q&T steels has been studied by means of dilatometry, hardness measurements, and scanning electron microscopy. The heating rate, as well as the direction and level of applied stress, have been varied. The results have proven the existence of TRIP strain during continuous tempering and its linear dependence on the fraction of the precipitates. A higher amount of carbon results in a growth of the precipitates surface area percentage, leading to an increase in the TRIP strain and consequently the TRIP constant. This indicates the presence of the Greenwood–Johnson effect, which relates TRIP to the difference in volume between the existing and forming phases.